2017
DOI: 10.1111/jon.12452
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Ultrasound of the Vagus Nerve in Patients with Diabetes

Abstract: This study demonstrates a degree of vagus nerve atrophy in patients with diabetes. This finding may have relevance in the diagnosis and treatment of diabetic neuropathy if further validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
51
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 28 publications
7
51
6
Order By: Relevance
“…In diabetes, CSA has been reported to be decreased in the vagus nerve and increased in peripheral nerves . Present data confirm the recently reported right‐left differences in vagus nerve diameters .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In diabetes, CSA has been reported to be decreased in the vagus nerve and increased in peripheral nerves . Present data confirm the recently reported right‐left differences in vagus nerve diameters .…”
Section: Discussionsupporting
confidence: 91%
“…However, HR‐US systems are now available that provide online area measures as square millimeters with 1 or more (up to 3) digits after the decimal point, an option that can be chosen by the user in the system settings . The measures of vagus nerve CSA in the present study are lower than values reported earlier for a normal population . This can be explained by the more precise method applied here for calculating CSA.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations